The Impact of Railway Noise Upon the Quality of Life - Michael Sophian Putra; Ratna Kusumawati; R. Prihandjojo Andri Putranto (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2017)
Introduction: Railway noise is an unexpected noise caused by either the machine of the trains or the friction between the wheels and the railroads. Long lasting noise has a negative impact upon psychological condition, mental function, and the quality of ones life. The aim of this study was to know whether there was an impact of the railway noise upon the quality of life of the society living at the banks of railroads in Nusukan, Surakarta. Methods: This was an observational analytic research with a cross sectional study. This research was done in Nusukan neighborhood, Banjarsari subregency, Surakarta town, from October to November 2015. The subject of the research was the society living at the banks of the railroads in Nusukan for the minimum of 1 year, men, and between 20-59 years of age. The sample taking was done by using purposive sampling technique as many as 60 people consisting of 30 respondents exposed by the railway noise of > 55dB and 30 respondents exposed by the railway noise of ? 55dB. The measurement of the noise was done by using a sound level meter device. The measurement upon the quality of life was made by using questionnaire of Nottingham Health Profile (NHP). The data were analyzed with unpaired t test (? = 0.05). Result: The result of the unpaired t test showed the average score of the quality of life of the respondents exposed by the railway noise of > 55dB was significant lower than that of the respondents exposed by the railway noise of ? 55dB, with p = 0.000 (P < 0.05). Conclusion: Respondents exposed by the railway noise of less than or as much as the threshold value (? 55dB) had better average quality of life than the respondent exposed by the railway noise which was higher than the threshold value (> 55dB). Keywords: Quality of life, railway noise, Nottingham Health Profile (NHP)